2013
DOI: 10.2478/s11535-013-0270-1
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccine and learning in C57BL mice with an acute experimental autoimmune encephalomyelitis

Abstract: Literature data suggest possible link between influenza vaccination and development of autoimmune processes. Therefore, the aim of the study was to investigate the effect of influenza vaccination on spatial learning in mice with experimental autoimmune encephalomyelitis (EAE). EAE was induced in eight-week-old C57BL/6J female mice by subcutaneous immunization (MOG35–55 in complete Freund’s adjuvant) and Pertussis vaccine injected intraperitoneally. Mice were vaccinated with influenza vaccine three days before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Our findings mainly confirm that there is no effect of influenza split vaccination on memory impairment in MOG induced EAE mice and no significant influence on hippocampal-dependent spatial learning. Additionally, although clinical signs of EAE are very subtle, the lesions that have been found in the hippocampal region of the brain could be associated with memory dysfunction observed during the course of MWM testing 114 . Even though the initial studies have demonstrated that influenza infection induces deficits in spatial learning and memory loss in adult mice at day 7 post infection, conflicting data exist regarding the connection between MS and other autoimmune illnesses and vaccination 95,111 .…”
Section: Influenza Vaccine Impact On Spatial Learning and Memory In Msmentioning
confidence: 99%
“…Our findings mainly confirm that there is no effect of influenza split vaccination on memory impairment in MOG induced EAE mice and no significant influence on hippocampal-dependent spatial learning. Additionally, although clinical signs of EAE are very subtle, the lesions that have been found in the hippocampal region of the brain could be associated with memory dysfunction observed during the course of MWM testing 114 . Even though the initial studies have demonstrated that influenza infection induces deficits in spatial learning and memory loss in adult mice at day 7 post infection, conflicting data exist regarding the connection between MS and other autoimmune illnesses and vaccination 95,111 .…”
Section: Influenza Vaccine Impact On Spatial Learning and Memory In Msmentioning
confidence: 99%